Fatal intoxication with N-ethylpentylone: a case report - Chisom Ikeji; Charmian D. Sittambalam; Lyn M. Camire; David S. Weisman (Greater Baltimore Medical Center, 2018)
Synthetic cathinones represent the latest genre of new drugs of abuse, which are increasing in popularity in part because they are readily available and because they are not detected by routine drug testing. They provide a cheaper substitute to stimulants such as methamphetamine and cocaine and are sold on the internet and in retail establishments as 'bath salts,' 'plant food,' or 'research chemicals.' We report a case involving a 21-year-old male who suffered arrest-related death due to intoxication with N-ethylpentylone, a new cathinone derivative. He reportedly left his house to smoke marijuana and returned displaying extremely odd behavior. The patient was unresponsive upon presentation to the emergency room and was intubated after suffering cardiac arrest. Clinical laboratory values revealed elevated lactic acidosis, hyperkalemia, rhabdomyolysis, and renal injury. His condition continued to worsen despite medical management. Sudden cardiac arrest occurred again 72 hours into his hospital stay and the patient was pronounced dead. Post-mortem toxicology testing with gas chromatography and mass spectrometry determined the presence of N-ethylpentylone in the urine. This case report details the behavior effects, clinical presentation, and autopsy findings for N-ethylpentylone drug intoxication.